Just what kind of mother are you? - Daly, Paula (Great Britain : Bantam Books, 2013)
Lisa Kallisto is one of those overworked, overscheduled mothers who never secures enough sleep at night. After getting her three kids off to school, working all day as the manager of a charitable animal shelter and taking care of her household, she's lucky to get a few minutes to herself. So when her daughter's friend Lucinda turns up missing after she was supposed to spend the night at Lisa's home, Lisa is full of blame and self-loathing. And she's not the only one who finds herself at fault: Most of Lucinda's family, the police and even her own husband, Joe, think Lisa should have paid more attention to what the two young teens were doing. Now, it looks like the kidnapper, who has already abducted one other girl, is at it again, and Lisa is trying to put the pieces together. So is Joanne Aspinall, an investigator with the local police in the small English town where both Lisa's and Lucinda's families live, and Joanne's finding that things are growing more and more curious as the pieces to the puzzle refuse to fit together --
Originally published: Great Britain : Bantam Press, 2013.
PBK.
Keywords: Kidnapping -- Fiction; Guilt -- Fiction; Teenagers -- Fiction; Mothers -- Fiction; Guilt; Kidnapping; Mothers; Teenagers; Fiction; Suspense fiction; Mystery fiction